The Role of Teachers and Students in the Islamic Tradition of the Classical Period - Hilwa, Shofwatun; Tanjung, Indri; Nasution, Abdusima (Ahlussunnah: Journal of Islamic Education, 2025)
The Islamic tradition during the classical era made a significant contribution to the formation of civilization in education and the development of science. This discussion includes the roles of teachers and students in the classical Islamic tradition, emphasizing educational relationships, scientific ethics, and the methods of knowledge transmission that developed during that period. Teachers were positioned not only as transmitters of knowledge but also as moral and spiritual role models possessing scientific authority and moral integrity. Meanwhile, students were viewed as active subjects in the learning process, who were required to possess good manners, sincerity, and a commitment to the pursuit of knowledge. The success of classical Islamic education was largely determined by a harmonious reciprocal relationship between teachers and students, grounded in religious, ethical, and spiritual values. This is relevant for reflecting on the contemporary educational process so that it focuses not only on cognitive aspects but also on the development of students' character and morals.